The Effect of Exclusive Breastfeeding on The Acidity Level of Infant's Feces - Asri Noviyanti (Science Midwifery, 2022)
Breast Milk is important to support the growth of the composition of an infant's gut after birth. Breast milk contains bacteria that are beneficial to the infant’s gut. These bacteria play the role to inhibit the growth of harmful bacteria in an infant’s body that can cause infections with keeping the acidity of the infant’s gut. This study aims to determine the relationship of the total colony of LAB in breast milk and pH feces or infant based on the stage of lactation. This study was an observational study with a cross-sectional design conducted on 25 postpartum mothers who breastfed exclusively in the working territory of Andalas, Ambacang, and Ikur Koto Community Health Center, Padang. Samples were selected by consecutive sampling. Data normality was tested by Shapiro-Wilk, Friedman test for assessing difference, Spearman and Pearson correlation test to assess the correlation between total colony lactic acid bacteria in breast milk and pH feces of infants. The result shows a significant difference in total colony LAB in lactation stage with p=0,021 (p<0,05) and median the highest LAB in colostrum is 2600000 CFU/ml. And significant difference pH infant’s feces with p=0,001 (p<0,05) and median on transitional stage is 5,42. The result show was a significant correlation between total colony lactic acid bacteria in breast milk and pH feces of infants on transitional stage with p=0,001 (r=-0,729)